Force-sensing hangboard to enhance finger training in rock climbers - Anderson, M. (Proceedings, 2018)
In rock climbing, finger strength is directly related to performance. Here, a novel device is described to enhance finger strength training or aid in rehabilitation of finger injuries. The device incorporates load cells into an existing hangboard to measure finger force, record it and display it to the athlete in real time. The device was characterized for accuracy, linearity, hysteresis and repeatability, and found to have a resolution of ±01.5 N, sample rate of 10 Hz, and linearity of 0.9998. Preliminary athlete trials of the device verified its ability to more accurately record training exertion, that biases exist between the right and left hands of climbers and that this real-time performance feedback can improve training quality.